Measurement of the semileptonic charge asymmetry in B0 meson mixing with the D0 detector - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; Avila, C.; et al. (American Physical Society (APS), 2012)
We present a measurement of the semileptonic mixing asymmetry for B0 mesons, asld, using two independent decay channels: B0→μ +D -X, with D -→K +π -π -; and B0→μ +D *-X, with D * -→D ̄0π -, D ̄0→ K +π - (and charge conjugate processes). We use a data sample corresponding to 10.4fb -1 of pp̄ collisions at √s=1.96TeV, collected with the D0 experiment at the Fermilab Tevatron collider. We extract the charge asymmetries in these two channels as a function of the visible proper decay length of the B0 meson, correct for detector-related asymmetries using data-driven methods, and account for dilution from charge-symmetric processes using Monte Carlo simulation. The final measurement combines four signal visible proper decay length regions for each channel, yielding asld=[0.68±0.45(stat)±0.14(syst)]%. This is the single most precise measurement of this parameter, with uncertainties smaller than the current world average of B factory measurements. © 2012 American Physical Society.